Analisis Pengaruh Foreign Direct Investment dan Perdagangan Internasional Terhadap Penyerapan Tenaga Kerja Di Asean-5 - Gaillardia Arifa Almas (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
The purpose of this research is to determine the effect of Foreign Direct Investment and International Trade (Export-Import) on Labor Absorption in ASEAN-5. By using a quantitative approach. The analytical tool used is panel data regression analysis with the Fixed Effect Model approach using Eviews 9 software. With this analysis, the results obtained if the variables of Foreign Direct Investment in ASEAN-5 countries and Export and Import have a significant effect simultaneously with the independent variables contributing 93.1 % of the dependent variable, while the remaining 6.9% is explained by other variables not included in this study. The partial test results show that the value of Foreign Direct Investment, Exports and Imports in ASEAN-5 has a significant positive effect on the value of Labor Absorption in ASEAN-5 Countries.